Development and thermal requirements of Trichogramma pretiosum Riley, rearing in two tomato leafminer - Pratissoli, Dirceu; Parra, José Roberto Postali (Pesquisa Agropecuaria Brasileira, 2000)
The biology of Trichogramma pretiosum in eggs of Phthorimaea operculella (Zeller) and of Tuta absoluta (Meyrick) were studied under different temperatures (18, 20, 22, 25, 30, 32°C), 70±10% RU and photophase of 14 hours, with the aim of determining the thermal requirements and the number of generations during the year. There was an inverse correlation between the duration of the cycle and the increase of temperature in the thermal zone studied. Nevertheless, the sexual ratio was not affected by the temperature when the host was T. absoluta. The viability of T. pretiosum, reared in P. operculella, was more affected than in T. absoluta. The thermal requirement, calculated by the hyperbole was higher for T. absoluta (131.3 degrees day) in relation to P. operculella (120.9 degrees day), and the thermal threshold was lesser respectively, 12.98oC and 13.53°C. For both species of leafminer, the longevity of parasitoid always obeyed the Weibull's distribution. The increase of the potential was estimated for both species of leafminer, according to the number of annual generations.